2011
DOI: 10.1074/jbc.m111.277434
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species and p38 Mitogen-activated Protein Kinase Mediate Tumor Necrosis Factor α-Converting Enzyme (TACE/ADAM-17) Activation in Primary Human Monocytes

Abstract: Background:The mechanisms responsible for up-regulation of TNF␣-converting enzyme (TACE) catalytic activity in primary human monocytes have not been elucidated. Results: TACE activation by lipopolysaccharide was dependent on reactive oxygen species (ROS) and the p38 MAPK pathway. Conclusion: ROS mediate TACE catalytic activation indirectly through the p38 pathway. Significance: This redefines the mechanisms of TACE activation in primary cells with a physiological stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 66 publications
(82 reference statements)
6
80
0
1
Order By: Relevance
“…It is thought that endothelial TACE is activated by mitochondrial reactive oxygen species in response to changes in calcium levels. In other models and in CHO or HL-60 cells, TACE activation has been shown to be ATP-(60), calcium-, or mitogen-activated protein kinase-dependent (61)(62)(63). Nitrosylation of TACE in macrophages has been shown to be involved in TACE activation for TNF␣ maturation (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that endothelial TACE is activated by mitochondrial reactive oxygen species in response to changes in calcium levels. In other models and in CHO or HL-60 cells, TACE activation has been shown to be ATP-(60), calcium-, or mitogen-activated protein kinase-dependent (61)(62)(63). Nitrosylation of TACE in macrophages has been shown to be involved in TACE activation for TNF␣ maturation (33).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that TACE can be phosphorylated by kinases, such as p38 MAPK. This kinase has been found to phosphorylate TACE in lymphocytes and monocytes (62). Phosphorylation of the cytoplasmic domain of TACE can occur not only on a threonine but also on a serine (55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…We next examined mechanisms for NOD2-induced early TACE activation. The MAPK p38 can induce TACE activity (27). ERK, p38, JNK, and NF-κB activation were required for NOD2-induced early TACE activity and TNFSF15 processing (Fig.…”
Section: Tnfsf15 Stimulates Dr3 To Initiate Downstream Signaling Requmentioning
confidence: 99%
“…Trovafloxacin Increases LPS-Induced TNF Release in RAW Cells involve p38 at several levels: activation of trans-acting factors, stabilization of TNF mRNA, and shedding of membrane-bound TNF (Deleault et al, 2008;Rowlett et al, 2008;Scott et al, 2011). Surprisingly, p38 inhibition failed to alter the TVXmediated increase in TNF mRNA (Fig.…”
Section: Discussionmentioning
confidence: 93%